how do you figure out whether f(x) = (4/7)x + (8/7) has the inverse of g(x) = -2 + (7/4)x or not?

And how do you get the inverse of f(x)( -3/4)x - 3?

Thank you for the opportunity to help you with your question!

f(x) = (4/7)x + (8/7)

=> f(x) -8/7 = (4/7)x

=> (7/4) f(x) -7/4)(8/7) = x

replacing f(x) by x and x by g(x) we have

g(x) = (7/4)x -2

so g(x) is the inverse of f(x)

b) f(x) = -(3/4)x -3

=> f(x) +3 = (-3/4)x

-(4/3) f(x) +3(-4/3) = x

replacing f(x) by x and x by g(x) we get

-(4/3)x -4 = g(x)

g(x) is the inverse of f(x)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up